Unconventional superconductivity in the strong-coupling limit for the heavy fermion system CeCoIn5 - Fasano, Y. (2018)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina; Universidad Nacional de Cuyo; Argentina